How can brands become central in the consumers’ life? - Arnold Japutra; Sandra Maria Correia Loureiro; Shasha Wang; Haryani Primanti (Spanish Journal of Marketing-ESIC, 2023)
Purpose – Brand centrality is a religion-like brand–customer relationship, which refers to the extent to which a brand is in the center or heart of a consumer’s life. While its role in the fast fashion industry is prominent, its drivers and effects have not been comprehensively studied. This study aims to investigate the relationships between three psychological drivers (i.e. fashion-conscious, chronic shopping orientation and self-esteem), one behavioral driver (i.e. the average frequency of shopping), brand centrality and relationship quality in the fast fashion industry. Design/methodology/approach – A survey of 250 fast fashion consumers was conducted and partial least squares-structural equation modeling (PLS-SEM) was used to analyze the data. Findings – The study shows that fashion consciousness and chronic shopping orientation are positively related to brand centrality, whereas self-esteem is negatively related to brand centrality. The findings also show that shopping frequency moderates the relationship between fashion consciousness and brand centrality, and between chronic shopping orientation and brand centrality. Post hoc analysis indicates that brand centrality fully mediates the relationship between chronic shopping orientation and relationship quality. Originality/value – This study is one of the first studies to investigate the psychological and behavioral drivers of brand centrality. ¿Cómo pueden las marcas ocupar un lugar Central en la vida de los consumidores? Objetivo – La centralidad de la marca es una relación religiosa entre marca y cliente que se refiere al grado en que una marca está en el centro o corazón de la vida de un consumidor. Aunque su papel en la industria de la moda rápida es destacado, sus impulsores y efectos no se han estudiado exhaustivamente. El presente estudio investiga las relaciones entre tres impulsores psicológicos (la conciencia de la moda, la orientación a las compras crónicas y la autoestima), un impulsor conductual (la frecuencia media de las compras), la centralidad de la marca y la calidad de las relaciones en el sector de la moda rápida. Diseño – Se realizó una encuesta a 250 consumidores de moda rápida y se utilizó (PLS-SEM) para analizar los datos. Resultados – El estudio muestra que la conciencia de la moda y la orientación a las compras crónicas están positivamente relacionadas con la centralidad de marca, mientras que la autoestima está negativamente relacionada con la centralidad de marca. Los resultados también muestran que la frecuencia de compra modera la relación entre la conciencia de la moda y la centralidad de marca, y entre la orientación de compra crónica y la centralidad de marca. El análisis post-hoc indica que la centralidad de la marca media totalmente la relación entre la orientación a las compras crónicas y la calidad de las relaciones. Originalidad – Este estudio es uno de los primeros en investigar los impulsores psicológicos y conductuales de la centralidad de marca. 目的 – 品牌中心性是一种类似于宗教的品牌-客户关系, 指的是一个品牌在消费者生活中处于中心或核心的程度。虽然它在快速时尚行业中的作用很突出, 但它的驱动和影响还没有得到全面的研究。本研究调查了三个心理驱动因素（即时尚意识、长期购物取向和自尊心）、一个行为驱动因素（即平均购物频率）、品牌中心性和快时尚行业的关系质量之间的关系。 设计/方法/途径 – 对250名快时尚消费者进行了调查, 并使用部分最小二乘法-结构方程模型（PLS-SEM）来分析数据。 结果 – 研究表明, 时尚意识和长期购物取向与品牌中心性呈正相关, 而自尊心与品牌中心性呈负相关。研究结果还显示, 购物频率分别调节了时尚意识以及长期购物导向对品牌中心性的影响。事后分析表明, 品牌中心性在长期购物取向和关系质量之间具有完全中介作用。 原创性/价值 – 本研究是最早研究品牌中心性的心理和行为驱动因素的研究之一。